2020
DOI: 10.2478/s11686-020-00198-y
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Associated Factors and Treatment Methods of Cutaneous Leishmaniasis Based on Previous Data from 2013 to 2018 in Ilam, Western Iran

Abstract: Objective The aim of this study was to evaluate the epidemiology, clinical presentation and types of treatment of cutaneous leishmaniasis (CL) in the province of Ilam (Western Iran) in 5 years (from May 2013 to January 2018). This cross-sectional study involved patients diagnosed with CL who were referred to Mehran City Health center. Methods All patients were diagnosed by clinical and parasitological (Giemsa staining of lesion to observe the parasite) methods. Moreover, a structured questionnaire on demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
4
2
0
Order By: Relevance
“…The disease is more prevalent in young age groups and patients under 10 years of age had the highest infection rate (64.3%), and the lowest infection rate (4.3%) was observed in people over 60 years old ( Table 1 ). This finding is in agreement with the results of previous studies carried out in known ZCL endemic regions of Iran including Ilam, Kerman, Fars, and Golestan Provinces ( Rezaee et al, 2020 ; Fakoorziba et al, 2011 ; Jorjani et al, 2019 ). Similarly, in studies conducted in Pakistan and Afghanistan the CL was more prevalent in young age groups ( Brooker et al, 2004 ; Faulde et al, 2008 ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The disease is more prevalent in young age groups and patients under 10 years of age had the highest infection rate (64.3%), and the lowest infection rate (4.3%) was observed in people over 60 years old ( Table 1 ). This finding is in agreement with the results of previous studies carried out in known ZCL endemic regions of Iran including Ilam, Kerman, Fars, and Golestan Provinces ( Rezaee et al, 2020 ; Fakoorziba et al, 2011 ; Jorjani et al, 2019 ). Similarly, in studies conducted in Pakistan and Afghanistan the CL was more prevalent in young age groups ( Brooker et al, 2004 ; Faulde et al, 2008 ).…”
Section: Resultssupporting
confidence: 93%
“…Men were infected more than women, with 45.7% of cases occurring in women over the studied period. This finding is in accordance with other epidemiologic studies in Iran which revealed higher incidence rate of CL in men ( Rostami et al, 2013 ; Mohammadi and Soltani, 2019 ; Nilforoushzadeh et al, 2014 ; Rezaee et al, 2020 ; Akhlagh et al, 2019 ). Similar findings have been reported from other endemic countries such as Saudi Arabia, Pakistan, Iraq, Syria, Jordan, Yemen, Libya, Algeria, Bolivia, and Brazil, where males had higher CL infection than females ( Abuzaid et al, 2017 ; Khan et al, 2016 ; AlSamarai and AlObaidi, 2009 ; Youssef et al, 2019 ; Salam et al, 2014 ; Alkulaibi et al, 2019 ; Khezzani and Bouchemal, 2017 ; Eid et al, 2018 ; Araujo et al, 2016 ; Krieger, 2003 ).…”
Section: Resultssupporting
confidence: 93%
“…According to the results of this study, the highest prevalence of the disease was in the winter and fall. This finding is in agreement with previous studies conducted in Iran, revealing a high prevalence of CL in the winter and fall seasons [33][34][35][36]. The seasonal trend of CL is associated with the known vector activity.…”
Section: Discussionsupporting
confidence: 93%
“…The result of this study also indicated that the lesions were mostly found on the face and hands. This finding is similar to the distribution pattern of the CL lesions reported from different CL endemic areas of Iran [12,13,[32][33][34]. The reason for this may be the short proboscis of sand flies, making them incapable of biting through clothing; therefore, they bite exposed parts of the body, including feet, hands, and face.…”
Section: Discussionsupporting
confidence: 85%
“…In Iran, two species of L. tropica and L. major are the causative agents of CL, with approximately 20,000 cases reported each year ( 6 ) . CL is estimated to be about 1.8%-37.9% in different rural provinces of Iran, with children being more affected (7). The clinical symptoms of CL vary depending on the species of the parasite, but usually, the disease begins with a papule or nodule, reaching its final size in about a week of slow growth.…”
Section: Introductionmentioning
confidence: 99%